2009
DOI: 10.1177/230949900901700102
|View full text |Cite
|
Sign up to set email alerts
|

Heparin versus Danaproid for Prevention of Venous Thromboembolism after Hip Surgery

Abstract: Danaproid sodium appeared more effective and safer than heparin, with no bleeding complications occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Hip fractures in particular are also associated with potentially severe complications like deep vein thrombosis, pressure ulcers, and pulmonary embolism, whereas vertebral fractures can affect pulmonary function (Schlaich et al , 1998; Margolis et al , 2003; Anand and Buch, 2007; Nakase et al , 2009). Our findings showed an increased overall mortality in breast cancer patients following hospitalisation with bone fracture that was interestingly independent of other comorbidities and tumour characteristics (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Hip fractures in particular are also associated with potentially severe complications like deep vein thrombosis, pressure ulcers, and pulmonary embolism, whereas vertebral fractures can affect pulmonary function (Schlaich et al , 1998; Margolis et al , 2003; Anand and Buch, 2007; Nakase et al , 2009). Our findings showed an increased overall mortality in breast cancer patients following hospitalisation with bone fracture that was interestingly independent of other comorbidities and tumour characteristics (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of danaparoid is its low rate of cross-reactivity with antibodies associated with immune-mediated heparin-induced thrombocytopenia [14]. Further, it has been reported that danaparoid sodium is unlikely to cause gastrointestinal hemorrhage, and it appears to be more effective and safer than heparin in terms of bleeding complications [15].…”
Section: Introductionmentioning
confidence: 99%
“…28 Danaparoid has been found to have less influence on platelets compared with other anticoagulants because it inhibits factor Xa selectively. 29 However, given the low incidence of HIT after TJA, LMWH is still able to be used as the chemoprophylaxis after TJA in patients without a history of HIT. 11,13,14 This study had several limitations.…”
Section: Discussionmentioning
confidence: 99%